The crisis of contemporary culture - Eagleton, Terry, 1943- (Oxford University Press, 1993)
This volume is an inaugural lecture delivered before the University of Oxford on 27 November 1992. T.F. Eagleton ranges widely over a number of topics of relevance to contemporary culture: the loss of a sense of corporate cultural identity in the contemporary crisis of "nationhood" and the factors responsible for this erosion; the conflict between a traditionalist conception of culture and a "postmodern" one; the assumed decline in cultural standards; and the teaching of English in schools. He sets forth the history and current situtation of Oxford English within this wider context, and outlines a programme of desirable reforms. He concludes his lecture with some reflections on peotry and philosophy, literary theory and multinational capitalism.